Education and Income: Significant Factors in Life Satisfaction of Farm Men and Women - Harriett K. Light; Doris Hertsgaard; Ruth E. Martin (Journal of Research in Rural Education, 1985)
The purpose of this study was to determine if life satisfaction as perceived by farm men and farm women differed significantly according to their age, gender, income, or education level. The Neugarten Life Satisfaction Index A (LSIA) was completed by 760 randomly selected farm residents in an upper midwest state. Significant differences were found between mean LSIA scores according to education level and income of subjects. Individual LSIA item analysis revealed significant differences on eleven out of twenty statements according to education level and on ten statements according to income level. Generally, as education and income level increased, life satisfaction also increased.